Pengaruh Penggunaan Model Problem Based Learning (PBL) Terhadap Perilaku Prososial dan Motivasi Belajar IPS di Kelas V SD Gugus IX Kota Bengkulu - Febby Intan Permata Sari; Badeni; Endang Widi Winarni (Jurnal Kajian Pendidikan Dasar, 2024)
This research aims to determine the effect of using the problem based model (PBL) on prosocial behavior and social studies learning motivation in class V of SD Gugus IX Bengkulu City. This type of research is quantitative research. The research method used is quasi experimental design with the type of design "the matching only pretest-posttest control group design." The population in this study was elementary school cluster IX in Bengkulu City. The sampling technique uses random sampling. The sample in this study was class VD SDN 82 Kota Bengkulu as the experimental class and class VB SDN 73 Kota Bengkulu as the control class. The research instrument used was a questionnaire on prosocial behavior and student learning motivation which was given through initial and final questionnaires in the experimental class and control class. The data analysis technique in this research is quantitative analysis using descriptive statistics and inferential statistics, namely the t-test. The research data were processed using the t-test by looking at the gain value, it was found that the t-count value of prosocial behavior was 15.77 and student learning motivation was 6.79 and the t-table value was 2.07. Statistically, it can be seen that tcount of prosocial behavior (15.77) and student learning motivation (6.79) > ttable (2.07) at the 5% significance level. Thus, it can be concluded that there is an influence of the use of the problem based learning model on social studies learning motivation in class V of SD Gugus IX Bengkulu City.